TARDBP/TDP-43 regulates autophagy in both MTORC1-dependent and MTORC1-independent manners. Issue 4 (2nd April 2016) - Ying, Zheng; Xia, Qin; Hao, Zongbing; Xu, Delai; Wang, Mingmei; Wang, Hongfeng; Wang, Guanghui
ABSTRACT: In a recent paper we addressed the mechanism by which defective autophagy contributes to TARDBP/TDP-43-mediated neurodegenerative disorders. We demonstrated that TARDBP regulates MTORC1-TFEB signaling by targeting RPTOR/raptor, a key component and an adaptor protein of MTORC1. Loss of TARDBP decreased the mRNA stability of RPTOR and this regulation in turn enhanced autophagosomal and lysosomal biogenesis in an MTORC1-dependent manner. Meanwhile, loss of TARDBP could also impair autophagosome-lysosome fusion in an MTORC1-independent manner. Importantly, we found that modulation of MTOR activity by treatment with rapamycin and phosphatidic acid had strong effects on the neurodegenerative phenotypes of TBPH ( Drosophila TARDBP)-depleted flies. Taken together, our data reveal that multiple dysfunctions in the autophagic process contribute to TARDBP-linked neurodegeneration and may help to identify potential therapeutic targets in the future.